Sobre a independência das três primeiras teses (151e-186e) no Teeteto de Platão. - Silva, Marcílio Diniz da (2012)
The dissertation concerns the problem of connection among the first three thesis in the platonic dialogue Theaetetus, that are 1) the thesis that says the epistēmē is aisthēsis (Theaetetus first answer to 'what is knowledge' question), 2) the Protagoras' thesis of the homo mensura and 3) the Fluxism thesis. We start exposing the connection problem among this thesis, defended by some authors as logically necessary (i.e. that the three thesis are really interconnected) and by others as not. Hereafter we examine the connection on the platonic text itself until the Protagoras' Defense (apologia Pratagorou) and its refutation (in 160e- 186e), towards a best understanding of the three thesis connection. At last, we finish our considerations and comments, arguing an answer on defensibility of the independence (considering that the thesis are not logically required one to another) of the three thesis.